Natural history of dental caries in very young Australian children. Issue 3 (13th May 2015) - Gussy, Mark; Ashbolt, Rosie; Carpenter, Lauren; Virgo‐Milton, Monica; Calache, Hanny; Dashper, Stuart; Leong, Pamela; de Silva, Andrea; de Livera, Alysha; Simpson, Julie; Waters, Elizabeth
Abstract : Background: Whilst the global burden of caries is increasing, the trajectory of decay in young children and the point at which prevention should occur has not been well established. Aim: To identify the 'natural history' of dental caries in early childhood. Design: A birth cohort study was established with 467 mother/child dyads followed at 1, 6, 12, 18, and 36 months of age. Parent‐completed surveys captured demographic, social, and behavioural data, and oral examinations provided clinical and data. Results: Eight per cent of children (95% confidence interval (CI): 5–12%) at 18 months and 23% (95% CI: 18–28%) at 36 months experienced decay. Interesting lesion behaviour was found between 18 and 36 months, with rapid development of new lesions on sound teeth (70% of teeth, 95% CI: 63–76%) and regression of many lesions from non‐cavitated lesions to sound (23% of teeth, 95% CI: 17–30%). Significant associations were found between soft drink consumption and lesion progression. Conclusions: Findings suggest optimal time periods for screening and prevention of a disease which significantly impacts multiple health and well‐being outcomes across the life course.